PERLINDUNGAN HUKUM NASABAH DALAM KASUS PEMBOBOLAN REKENING BANK DI INDONESIA - Almira Qurrotul Aini; Elanti Fatayatun Khoiroh (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
Abstrak : The legal protection of customers in cases of bank account breaches in Indonesia is an urgent issue in line with the increase in cybercrime targeting the banking sector. This article examines the regulation of legal protection for customers, including the liability of banks as stipulated in the Banking Law and the Consumer Protection Law. Findings show that while a clear legal framework exists, its implementation is often ineffective. Customers often suffer financial losses and face difficulties in resolving disputes with banks, both through litigation and non-litigation channels. This article highlights the importance of preventive measures by banks, such as improved security systems and customer education, as well as the role of regulators in ensuring banks' compliance with consumer protection standards. Through a normative juridical approach, this article provides a comprehensive overview of the challenges and solutions in strengthening customer legal protection to increase public confidence in the banking system.Keyword: Legal Protection, Customer, Account Breach, Banking. Abstrak : Perlindungan hukum nasabah dalam kasus pembobolan rekening bank di Indonesia merupakan isu mendesak seiring dengan meningkatnya kejahatan siber yang menargetkan sektor perbankan. Artikel ini mengkaji regulasi perlindungan hukum bagi nasabah, termasuk tanggung jawab bank sebagaimana diatur dalam Undang-Undang Perbankan dan Undang-Undang Perlindungan Konsumen. Temuan menunjukkan bahwa meskipun ada kerangka hukum yang jelas, implementasinya sering kali belum efektif. Nasabah kerap mengalami kerugian finansial dan menghadapi kesulitan dalam menyelesaikan sengketa dengan bank, baik melalui jalur litigasi maupun non-litigasi. Artikel ini menyoroti pentingnya langkah preventif oleh bank, seperti peningkatan sistem keamanan dan edukasi nasabah, serta peran regulator dalam memastikan kepatuhan bank terhadap standar perlindungan konsumen. Melalui pendekatan yuridis normatif, artikel ini memberikan gambaran menyeluruh tentang tantangan dan solusi dalam memperkuat perlindungan hukum nasabah guna meningkatkan kepercayaan publik terhadap sistem perbankan.Kata kunci: Perlindungan Hukum, Nasabah, Pembobolan Rekening, Perbankan.